1987
DOI: 10.1002/chin.198709197
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Benzodiazepines with Both Sedative and Analgesic Activities.

Abstract: 197 ChemInform Abstract The amine (I) is converted to the amide (III), which undergoes cyclization to give (IV) followed by reduction to the diazepin (Va). Hydrolysis or aroylation of (Va) leads to the acetic acid derivatives (Vb) or (VII), which are tested with regard to their antiinflammatory-analgesic and neuropsychopharmacological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Compounds 1-3 have been synthesized and purified as previously reported [23]. Deuterium labeling at the -NH position was obtained by dissolving 1 mg of parent ions are possible for these ionic species.…”
Section: Materials and Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 1-3 have been synthesized and purified as previously reported [23]. Deuterium labeling at the -NH position was obtained by dissolving 1 mg of parent ions are possible for these ionic species.…”
Section: Materials and Mass Spectrometrymentioning
confidence: 99%
“…In the course of research aimed at finding new anxiolitic agents, it was found that the tricyclic pyrrolo [1,2-a][l,4]benzodiazepine system possesses highly lipophilic and neurotropic properties. The introduction of appropriate substituents on this heterocycle yields biologically active compounds [19]. We wish to report here on the characterization by electron ionization, high-resolution, and tandem mass spectrometry of 5,6- (2), and the 4,6-dione derivative of 1 (3) (Scheme I), which are starting materials for the synthesis of new compounds that are pharmacologically active as serotonin 5-HT 1A receptor ligands [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is extensive research on pyrrolo [1,4]benzodiazepines (PBDs) [1][2][3] and some examples of dipyrrolodiazepine [4][5][6] and indolopyrrolobenzodiazepine [7,8] derivatives have been reported. Currently, there are a number of alkaloids with pyrrolo [1,4]benzodiazepine scaffold, exhibiting various properties, [9] including analgesic, [10,11] antifungal, [12,13] and cytotoxic [14] activities. Additionally, the human body contains specific benzodiazepine receptors, [15] so some PBDs have an effect on the nervous system demonstrating sedative [16] and antidepressant [17] effects.…”
Section: Introductionmentioning
confidence: 99%
“…The comparatively small number of publications on the [1,2- a ] and [1,2- d ] isomers is a reflection of the lesser interest in the biology of these compounds. Nevertheless, it is known that pyrrolo[1,2- a ][1,4]benzodiazepines exhibit a wide spectrum of biological effects, such as antinociceptive CNS [41,42], anti-inflammatory [41], analgesic [43] and fungicidal [44] activity, and are potent sedative [41,45,46], anticonvulsant [45,46], myorelaxant [45,47] and psychotropic [43,47] agents.…”
Section: Introductionmentioning
confidence: 99%